Exploring the dielectric properties of herbal medicine and modern pharmaceuticals: an integrative review - Khatri, Vinita; Dey, Prasanjit K. (Frontiers in Pharmacology, 2025)
The integration of herbal medicine with modern pharmaceuticals offers a novel approach to addressing complex healthcare challenges. This study investigates the role of dielectric spectroscopy in analysing key physicochemical properties such as solubility, stability, and molecular interactions. The findings reveal that combining herbal extracts with pharmaceutical agents enhances solubility and stability. It also reduces adverse effects, improving therapeutic efficacy. Dielectric spectroscopy is highlighted as a powerful analytical tool in this process. The study demonstrates how traditional herbal knowledge can be effectively linked with modern scientific methods. This approach enables the development of innovative therapeutic solutions that address safety and efficacy challenges. The results underline the potential of combining advanced analytical techniques with ethnopharmacological practices. This integration paves the way for the creation of safe, effective, and scientifically validated formulations for improved healthcare outcomes.